School Principal Management in Integrating Character Education: A Case Study of Realfunrainbow Kindergarten in Salatiga City - Maryani; Nurkolis; Muhtarom (Jurnal Paedagogy, 2026)
This study aims to examine the principal’s management in integrating character education at Realfunrainbow Kindergarten in Salatiga City. Character education in early childhood has become increasingly important in response to globalization, the rapid development of digital technology, and socio-cultural changes that influence children’s behavior. The study employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. Methodological triangulation was applied to ensure the credibility of the findings. The research participants included the principal, two Group B teachers, three parents as program beneficiaries, and three local MSME owners as internship partners. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal a distinctive innovation at Realfunrainbow Kindergarten, namely the integration of character education with local socio-economic contexts through internship programs at MSMEs. This initiative enables children to practice values such as discipline, cooperation, respect, and responsibility in authentic settings, thereby strengthening experiential learning and community engagement. In addition, the integration of character education is systematically implemented through the principal’s management functions, including planning, organizing, mobilizing, and controlling. Planning is based on needs analysis with a focus on character development, while organizing involves assigning teachers as mentors, engaging parents as collaborators, and establishing partnerships with local MSMEs. Mobilization is carried out through role modeling and motivation, whereas controlling is conducted through continuous supervision and evaluation. In conclusion, the successful integration of character education is largely determined by the principal’s managerial and leadership capacities in managing school resources comprehensively and sustainably, as well as in fostering community partnerships to support early childhood character development.